2016
DOI: 10.3823/2026
|View full text |Cite
|
Sign up to set email alerts
|

Resident Population In Institutions Of Long Stay For Elderly

Abstract: Objective: To describe the clinical and sociodemographic characteristics of elderly living in long-stay institutions in the municipality of João Pessoa. Method:Cross-sectional study, descriptive, population character.This study consisted of 324 elderly, living in six long-stay institutions for elderly in the municipality of João Pessoa. Data was collected by means of questionnaires to the elderly and/or responsible people, and analysis of patient records, and it was analyzed through descriptive statistics.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Osteoarticular diseases are those that affect bones, cartilage, tendons, and/or joints-temporary or permanent-and that cause mild, moderate, or severe disability [3], with the highest prevalence in older adults [4]. These pathologies are responsible for decreasing physical activity and for increasing falls and fractures, which contributes to loss of autonomy for daily activities and increases mortality and demand for public health services [5,6]. Some studies have concluded that these kinds of diseases could be related to heart diseases and to severe physical limitations when an upper limb is affected [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarticular diseases are those that affect bones, cartilage, tendons, and/or joints-temporary or permanent-and that cause mild, moderate, or severe disability [3], with the highest prevalence in older adults [4]. These pathologies are responsible for decreasing physical activity and for increasing falls and fractures, which contributes to loss of autonomy for daily activities and increases mortality and demand for public health services [5,6]. Some studies have concluded that these kinds of diseases could be related to heart diseases and to severe physical limitations when an upper limb is affected [7,8].…”
Section: Introductionmentioning
confidence: 99%